(untitled) (Ustozlar uchun, 2025)
This article provides information about the pragmatic features of expressions. The processes of emergence of expressions in the Uzbek language on the basis of the people’s lifestyle are highlighted. Opinions and comments on the linguistic and cultural research of pragma-phrases are presented.